ANALISIS MANAJEMEN SUMBER DAYA INSANI PADA KELOMPOK BIMBINGAN IBADAH HAJI DAN UMROH (KBIH) CAHAYA MULTAZAM - Cahyana, Dian; Isnaini, Nurul; Maulana, Rizky; Renfiana, Lilis (Institut Agama Islam Negeri Metro, 2023)
Recruitment, selection, training, skills development, and human resource performance appraisal activities are the pillars that form human resource management, which aims to obtain human resources who are experts and competent in their fields. Based on this, the authors conducted research on how human resource management is applied. The research uses qualitative methods with descriptive analysis. Data collection techniques were carried out by conducting interviews and KBIH Cahaya Multazam documentation. The results of the study stated that the recruitment process was carried out by selection. Training and development is carried out by gathering employees and inviting employees to make changes by developing creativity so that employees and KBIH Cahaya Multazam are better and become the congregation's choice. The performance evaluation itself is carried out on the basis and principles of honesty and employee loyalty to KBIH Cahaya Multazam.